Cerebral lateralization and religion: a phenomenological approach. Issue 4 (2nd October 2019) - McGilchrist, Iain
ABSTRACT: Both animal ethology and studies of the attentional styles of the two cerebral hemispheres in human subjects suggest that there is a degree of specialization, with the left hemisphere tending to focus more narrowly on detail, and the right hemisphere supporting sustained attention across a broad field. This has clear survival advantages. It also has consequences at the phenomenological level of integrated experience. Although both hemispheres are involved in all experience, the characteristics of right hemisphere phenomenology, in particular its greater capacity to sustain ambiguity, understand meaning that lies beyond language, and perceive systemic wholes, means that it is more likely to be able to accommodate religious thought and experience. Since critiques of religion tend to have the opposite characteristics (those of left hemisphere phenomenology), arguments about the nature and meaning of religion may depend on which hemisphere's "version" of the world is privileged. Some consequent metaphysical, epistemological and ethical issues are explored, drawing on brain studies and a range of other disciplinary and experiential perspectives.